Association between coping strategies, social support, and depression and anxiety symptoms among rural Ugandan women living with HIV/AIDS. Issue 7 (3rd July 2018) - Seffren, Victoria; Familiar, Itziar; Murray, Sarah M.; Augustinavicius, Jura; Boivin, Michael J.; Nakasujja, Noeline; Opoka, Robert; Bass, Judith
ABSTRACT: Poor mental health detrimentally affects quality of life among women living with HIV/AIDS. An improved understanding of how coping and social support relate to depression and anxiety in this population can facilitate the design and implementation of appropriate mental health treatment and support services. Secondary analysis was conducted on baseline data from 288 HIV-positive women enrolled in a parenting intervention in Uganda. Depression and anxiety symptoms, social support, and coping were assessed with the Hopkins Symptom Checklist and adapted versions of the Multidimensional Scale for Perceived Social Support and Ways of Coping Questionnaire. General linear regression models were used to estimate associations between coping and mental health. Based on report of elevated symptoms, approximately 10% of women were categorized as having clinically-relevant depression or anxiety. Emotion-focused (EF: p  < .001) and problem-focused (PF: p  = .01) coping were associated with more depressive symptoms while greater family support (EF: p  = .002; PF: p  = .003) was associated with fewer depression symptoms. More anxiety symptoms were associated with reporting both coping strategies (EF: p  < .001; PF: p  = .02) and higher community support (EF&PF: p  = .01). The cross-sectional nature of the study limits our ability to rule out the role of reverse causation in the significant relationship between coping and mental health. Findings do suggest that high family support can be protective against depression and anxiety symptoms among women living with HIV.